2004
DOI: 10.1093/ps/83.7.1232
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Carcass Washers on Campylobacter Contamination in Large Broiler Processing Plants

Abstract: Campylobacter, a major foodborne pathogen found in poultry products, remains a serious problem facing poultry processors. Campylobacter research has primarily focused on detection methods, prevalence, and detection on carcasses; limited research has been conducted on intervention. The aim of this study was to assess the effectiveness of carcass washing systems in 4 large broiler-processing plants in removing Campylobacter species. Washing systems evaluated included combinations of inside/outside carcass washer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
36
1
5

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(44 citation statements)
references
References 18 publications
2
36
1
5
Order By: Relevance
“…However, in this study, sodium hypochlorite was added at 10 ppm and chlorine dioxide at 50 ppm (USA, 1977), which are higher than the 5 ppm currently allowed in the Brazilian legislation. Bashor et al (2004) also reported that addition of chlorine at 25 to 35 ppm reduced Campylobacter spp. populations in broiler carcasses in 0.5 log CFU/mL of washing solution.…”
Section: Evaluation Of Disinfectants Used In Pre-chilling Water Tanksmentioning
confidence: 93%
“…However, in this study, sodium hypochlorite was added at 10 ppm and chlorine dioxide at 50 ppm (USA, 1977), which are higher than the 5 ppm currently allowed in the Brazilian legislation. Bashor et al (2004) also reported that addition of chlorine at 25 to 35 ppm reduced Campylobacter spp. populations in broiler carcasses in 0.5 log CFU/mL of washing solution.…”
Section: Evaluation Of Disinfectants Used In Pre-chilling Water Tanksmentioning
confidence: 93%
“…L'assainissement de l'eau par un traitement par le chlore permet la destruction rapide d'une contamination par Campylobacter. Le chlore est également utilisé aux Etats-Unis pour le nettoyage des carcasses et permet alors une réduction partielle de la population (0,5 log 10 UFC/ml après nettoyage avec de l'eau chlorée à 25-35 ppm) (BASHOR et al, 2004 …”
Section: Traitements Chimiques Atmosphères Modifiéesunclassified
“…The consumption and handling of poultry meat products is the major source of human campylobacteriosis, and the use of TSP during poultry meat processing is known to reduce levels of C. jejuni (4,28,29,37). The aim of the present study was to show whether sublethal TSP exposure affects gene expression and the physiology of C. jejuni, including cross-protection to other environmental stresses.…”
mentioning
confidence: 93%